Comparative evaluation of phosphorus accumulation and partitioning in seeds of common bean (Phaseolus vulgaris L.) - Piergiovanni, Angela Rosa; Lioi, Lucia; Montesano, Vincenzo; Sarli, Giulio (Italian Journal of Agronomy, 2017)
There is an increasing attention towards common bean due to its health benefits, prevention to human diseases and as ingredient for functional or fortified foods. Phosphorus, an essential element for plant growth, is mainly stored in seeds as phytic acid (Phy). Phy is negatively associated with mineral bioavailability, but, at the same time, is a natural antioxidant. Accumulation and partitioning of phosphorus were analysed in seeds of ten Italian common bean landraces for three subsequent growing seasons. Some important seed quality traits were also evaluated. For comparative purposes, the landrace harvests of two growing locations were analysed. A wide variation of total and phytic phosphorus contents was recorded among the landraces. Moreover, P accumulation and partitioning between Phy and inorganic P, as well as seed quality traits, resulted strongly affected by growing location. Statistically significant increases of Phy levels were recorded for harvests obtained outside the traditional area of cultivation. These results highlight how the cultivation of a landrace outside of its traditional area will appreciably affect harvest quality.